Translation and validation of vestibular rehabilitation questionnaire (pilot study) - Mohtar, Nurul Nabila; Wan Ahmad, Wan Aslynn Salwani; Mohd Sakeri, Nurul Syarida (IIUM Press, 2019)
Introduction: The purpose of this study is to adapt the Vestibular Rehabilitation Benefit Questionnaire (VRBQ) in order to cater for the limited availability of Malay vestibular questionnaire.